P122 Association between variability of respiratory sleep indices and ambulatory blood pressure. (9th November 2022) - Thant, A; Ou, Y; Seah, S; Chiu, S; Chan, S; Teo, Y; Wong, S; Khoo, C; Barbé, F; Lee, C
Abstract: Study Objectives: Respiratory sleep indices are traditionally reported on the basis of the average total sleep time. The relationship between the hour-to-hour variability of these parameters and blood pressure (BP) has not been reported. Methods: We evaluated the associations of the hour-to-hour variability of the apnea–hypopnea index (AHI), oxygen desaturation index (ODI), and lowest oxygen saturation with the 24-hour ambulatory BP in patients with hypertension and newly diagnosed obstructive sleep apnea. A total of 147 patients underwent polysomnography, based on which obstructive sleep apnea was diagnosed in 106 patients: these patients underwent 24-hour ambulatory BP monitoring within the next 30 days. Each polysomnogram was divided into hourly reports to calculate the variability of the respiratory sleep indices. Variability independent of the mean was considered the primary measure of variability. Results: The median number of hourly polysomnogram reports was 7 (range, 4–8).The hour-to-hour variability of both AHI and ODI, but not of the lowest oxygen saturation, was correlated with the 24-hour pulse pressure, 24-hour systolic BP, and awake systolic BP (p < 0.05 for all). The fully adjusted linear regression analysis indicated that the hour-to-hour variability of AHI and ODI remained associated with the 24-hour pulse pressure (AHI: β coefficient, 0.264 [95% CI, 0.033–0.495], p =0.026; ODI: β coefficient, 0.450 [95% CI, 0.174 - -0.726], p = 0.002). Conclusions: The hour-to-hour variability of AHI and ODI is independently associated with the 24-hour pulse pressure. Further investigations are warranted to evaluate the clinical relevance of this new-found association.